The Mysterious Treasure Map - Thomas, Jerry D.; Nang Chan Yeema (Nampa, ID USA Pacific Press Publishing Association, 1995)
When a map in an old book leads Chris on a treasure hunt with the Shoebox Kids, he learns that the real treasure in life is in following God.
Keywords: Story Collection